Investigating the Relationship between the Prevalence of Occupational Accidents with Individual and Occupational Factors in the Workplace. Case Study: Industries of Qom Province - Azam BIABANI; Mojtaba ZOKAIE; Mohsen FALAHATI (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Introduction: Investigations of accidents in industry have shown that various factors affect the occurrence of accidents. Therefore, the aim of this study was to investigate the relationship between the prevalence of occupational accidents with individual and occupational factors in the industrial work environment of Qom province. Methods: This descriptive study was performed based on the incidents registered in the Labor Inspection Office of Qom Province in 2017. All cases were selected and 1048 cases were reviewed according to the accurate registration of incidents. Necessary parameters were extracted from accident reporting forms and their frequency and frequency percentage were analyzed by SPSS 18 software. Results: The highest number of accidents was in the age range of 20-30 years with less than 5 years of work experience. The lowest number of accidents was related to bachelor's degree and higher. In addition, a high number of victims (41.5%) were involved in construction activities. In the study of the working population, the highest number of accidents was related to workshops with a staff number of 10-24. In investigating the causes of accidents, 33.2% of accidents were identified as lack of safety training and 24.2% as lack of safe work procedures. In the group of equipment causes, the highest share of accidents was due to the lack of proper equipment and in relation to human causes, the main reason for the accident was the non-stopping of the device during repair. Conclusion: The results of the present study showed that demographic and occupational factors, such as age, work experience, and type of industry were very important in the occurrence of industrial accidents. In addition, it was found that managerial, equipment and human causes each have an effective role in the occurrence of accidents, which can be significantly reduced using more supervision by managers and recruiting safety and health officials, and finally observing safety principles in all areas of work.